Preventing Digital Financial Harm in Rural Areas: Community Literacy on Illegal Online Loans and Online Gambling - Sajida, Sajida; Prasetya, Gregorius Christian Yoga; Farrel, Muhammad Arka Dito Al (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The rapid expansion of digital technologies has intensified financial misinformation and disinformation, particularly through illegal online loans and online gambling targeting communities with limited digital and financial literacy. This community engagement program in Dusun Munggur, Girimulyo Village, aimed to strengthen residents’ ability to identify and respond to deceptive digital practices through contextualized education on risk indicators, manipulative design strategies, and verification methods. Using a three-hour interactive socialization combining visuals, discussion, and a short comprehension exercise, the program improved participants’ understanding of how fraudulent financial schemes operate and how personal data, behavioral triggers, and algorithmic amplification are exploited. Participants demonstrated greater awareness of suspicious platforms, increased confidence in evaluating online offers, and requested sustained resources such as booklets and reporting guides for household- and community-level prevention. Although effective in raising immediate awareness, the intervention was limited by the lack of long-term behavioral assessment and the rapidly evolving nature of digital fraud. The program underscores the importance of community-centered, preventive literacy to mitigate digital financial risks in rural Indonesia.